Development of a New Type of Aluminum - Based Sacrificial Anode for Separator - XI Yun - tao, CHEN Wen - hao, LIU Rui, HE Jian - guo, XU Shan - na (Cailiao Baohu, 2021)
The aluminum alloy sacrificial anode used in oil and gas field separators has the problems of low current efficiency and local block loss during the service. According to the national standard, Zn, In, Mg and Ti with different contents were added in the alloy and the influences of alloying element contents on anode current efficiency and dissolution performance were studied by means of orthogonal experiment method to develop a new kind of high efficiency sacrificial anode. Results showed that the effect of Mg and Zn on the current efficiency was greater than that of In and Ti, and the influence trend of the change of each element content on the current efficiency was different. Mg content was the main factor influencing anode corrosion uniformity, which formed a second phase in the aluminum alloy anode, leading to changes in the local surface potential, and then forming a local micro - battery, eventually, the local corrosion of the anode surface was accelerated. Ti element played a role in the grain refinement. If the two contents of Mg and Ti were not properly matched, it would cause serious local segregation, causing the anode falling - block problem. Based on the range analysis of orthogonal test, the optimal combination of sacrificial anode formulation was 0.5%Mg - 4%Zn - 0.035%In - 0.045%Ti, which could significantly increase the current efficiency of the sacrificial anode and improve the dissolution uniformity of the sample.